The structure and biogeography of rainforest ant communities in the Kimberley region of north-western Australia - Majer, Jonathan; Anderson, A. N. (1991)
The ant faunas of eight rainforest patches in the seasonally arid Kimberley region are described from the results of pitfall traps, litter extractions, biscuit and tuna baits, beating vegetation and general hand-collections. Sampling was conducted during the dry season (June) of 1988, with supplementary litter samples collected dUring the following wet season. A total of 102 species (19-41 per patch, mean 33) from 33 genera were recorded, with the richest genera being Pheldole (13 species), Monomonum (12) and Polyrhachis (10). Arid-adapted genera such as tridomyrmex and Melophorus were Virtually absent. Forty-six species were considered to belong to Torreslan taxa, three to Eyrean taxa, five to Basslan taxa, and 48 to widespread taxa. Surrounding open sclerophyll habitats support a far greater proportion of Eyrean taxa, and lesser proportion of Torresian taxa. This survey provides baseline data for monitoring any future change In the Kimberley rainforest habitats.